Montage Mastery Revolutionizes Global Children's Motor Skills: Penguasaan Montase Merevolusi Keterampilan Motorik Anak Secara Global - Fariska, Vira Aulia; Nisak Aulina, Choirun (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the effectiveness of Pictorial Montage activities in enhancing fine motor skills among 5-6-year-old children in group B. Conducted through Classroom Action Research (CAR) with iterative cycles, the research involved 11 students from TK Tunas Bangsa Sukodono. Data collection included observation, interviews, and documentation. Results showed a gradual increase from 47% in pre-cycle to 90.1% in cycle II, indicating success in improving fine motor skills. These findings underscore the importance of engaging methods like Pictorial Montage for effective motor skill development in early childhood education. Highlight: Montage enhances motor skills in children. Iterative CAR method for skill assessment. Notable improvement in fine motor proficiency. Keyword: Fine motor skills, Pictorial Montage, Early childhood education, Classroom Action Research, Skill enhancement